Carbon-ion radiotherapy (CIRT) as treatment of pancreatic cancer at HIT: initial radiation plan analysis of the prospective phase II PACK-study - Baltazar, Filipa; Tessonnier, Thomas; Haberer, Thomas; Debus, Jürgen; Herfarth, Klaus; Tawk, Bouchra; Knoll, Maximilian; Abdollahi, Amir; Liermann, Jakob; Mairani, Andrea (Radiotherapy and oncology, 2023)
Purpose - To analyze the dose objectives and constraints applied at the prospective phase II PACK-study at Heidelberg ion therapy center (HIT) for different radiobiological models. - Methods - Treatment plans of 14 patients from the PACK-study were analyzed and recomputed in terms of physical, biological dose and dose-averaged linear energy transfer (LETd). Both LEM-I (local effect model 1) and the adapted NIRS-MKM (microdosimetric kinetic model), were used for relative biological effectiveness (RBE)-weighted dose calculations (DBio|HIT and DBio|NIRS). A new constraint to the gastrointestinal (GI) tract was derived from the National Institute of Radiological Science (NIRS) clinical experience and considered for plan reoptimization (DBio|NIRS-const_48Gy and DBio|NIRS-const_50.4Gy). The Lyman-Kutcher-Burman (LKB) model of Normal Tissue Complication Probability (NTCP) for GI toxicity endpoints was computed. Furthermore, the computed LETd distribution was evaluated and correlated with Local Control (LC). - Results - Only two patients showed a LETd98% in the GTV greater than 44 keV/μm. A HIT-dose constraint to the GI of D2cm3=48.6GyRBEHIT was derived from the NIRS experience, in alternative to the standard at HIT Dmax = 45.6 GyRBEHIT. In comparison with the original DBio|HIT, DBio|NIRS-const_48GyandDBio|NIRS-const_50.4Gy resulted in an increase in the ITV’s D98% of 8.7% and 11.3%. The NTCP calculation resulted in a probability for gastrointestinal bleeding of 4.5%, 12.3% and 13.0%, for DBio|NIRS, DBio|NIRS-const_48Gy and DBio|NIRS-const_50.4Gy, respectively. - Conclusion - The results indicate that the current standards applied at HIT for CIRT closely align with the Japanese experience. However, to enhance tumor coverage, a more relaxed constraint on the GI tract may be considered. As the PACK-trial progresses, further analyses of various clinical endpoints are anticipated.
Online verfügbar: 25. August 2023, Artikelversion: 12. September 2023
Gesehen am 05.12.2023